2016
DOI: 10.1002/jbm.b.33743
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline-incorporated polymer nanofibers as a potential dental implant surface modifier

Abstract: This study investigated the antimicrobial and osteogenic properties of titanium (Ti) disks superficially modified with tetracycline (TCH)-incorporated polymer nanofibers. The experiments were carried out in two phases. The first phase dealt with the synthesis and characterization (i.e., morphology, mechanical strength, drug release, antimicrobial activity, and cytocompatibility) of TCH-incorporated fibers. The second phase was dedicated to evaluating both the antimicrobial and murine-derived osteoprecursor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
0
28
0
3
Order By: Relevance
“…Our ongoing research focuses on synthesizing antibiotic-containing nanofibers on titanium dental implants [33] to first study in vitro the antimicrobial properties against a multispecies peri-implantitis-relevant biofilm, and later to evaluate its effects on a pre-clinical animal model. Taken together, this study demonstrated that antibiotic-containing fibers can effectively inhibit peri-implantitis-related biofilm formation, suggesting that tetracycline fibers hold great potential as an antibacterial implant coating.…”
Section: Resultsmentioning
confidence: 99%
“…Our ongoing research focuses on synthesizing antibiotic-containing nanofibers on titanium dental implants [33] to first study in vitro the antimicrobial properties against a multispecies peri-implantitis-relevant biofilm, and later to evaluate its effects on a pre-clinical animal model. Taken together, this study demonstrated that antibiotic-containing fibers can effectively inhibit peri-implantitis-related biofilm formation, suggesting that tetracycline fibers hold great potential as an antibacterial implant coating.…”
Section: Resultsmentioning
confidence: 99%
“…Application Oral Diseases Composition micro/nano particles micro/nano sphere dental caries [31,35] periodontitis [38] implant coating [50,51] oral candidiasis [52] PLGA, PDLLA, PEG and biopolymers like lipid, chitosan, pectin, and alginate nanofiber periodontitis [19] oral candidiasis [53] implant coating [43] nano capsule dental resin modification [42] hydrogel dental caries [54] periodontitis [55,56] oral candidiasis [57] Hydrophilic groups such as -OH, -CONH-, -CONH2dendrimer dental caries [58] PAMAM, poly(aryl ether) Figure 1. Examples of the structures of different kinds of carriers.…”
Section: Types Of Carriersmentioning
confidence: 99%
“…For example, some nanoparticles and nano capsules have been added to dental resin for caries prevention loaded with anti-bacterial agents while nanofibers can be coating on dental implants as since they could act as a scaffold for tissue regeneration. Recently, research has also reported pH-responsive nanoparticles that could respond to the acidic oral environment [42,43]. The nanoparticles modified with pH-sensitive groups such as tertiary amine showed structural changes in acid, thus leading to trigged drug release [47].…”
Section: Micro/nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations